Evaluation of the regenerative capacity of stem cells combined with bone graft material and collagen matrix using a rabbit calvarial defect model - Park, Jun-Beom; Kim, InSoo; Lee, Won; Kim, Heesung (Journal of periodontal & implant science, 2023)
The purpose of this study was to evaluate the regenerative capacity of stem cells combined with bone graft material and a collagen matrix in rabbit calvarial defect models according to the type and form of the scaffolds, which included type I collagen matrix and synthetic bone. Mesenchymal stem cells (MSCs) were obtained from the periosteum of participants. Four symmetrical 6-mm-diameter circular defects were made in New Zealand white rabbits using a trephine drill. The defects were grafted with (1) group 1: synthetic bone (β-tricalcium phosphate/hydroxyapatite [β-TCP/HA]) and 1×10 MSCs; (2) group 2: collagen matrix and 1×10 MSCs; (3) group 3: β-TCP/HA, collagen matrix covering β-TCP/HA, and 1×10 MSCs; or (4) group 4: β-TCP/HA, chipped collagen matrix mixed with β-TCP/HA, and 1×10 MSCs. Cellular viability and cell migration rates were analyzed. Uneventful healing was achieved in all areas where the defects were made at 4 weeks, and no signs of infection were identified during the healing period or at the time of retrieval. New bone formation was more evident in groups 3 and 4 than in the other groups. A densitometric analysis of the calvarium at 8 weeks post-surgery showed the highest values in group 3. This study showed that the highest regeneration was found when the stem cells were applied to synthetic bone along with a collagen matrix.